Current management practices do not adequately safeguard endangered plant species in conservation collections. (April 2023) - Diaz-Martin, Zoe; Fant, Jeremie; Havens, Kayri; Cinea, William; Tucker Lima, Joanna M.; Griffith, M. Patrick
Abstract: Imperiled plant species can benefit from ex situ cultivation to safeguard against loss of genetic diversity and possible extinction in the wild. Few studies use genetic monitoring in endangered plant species to evaluate how well current management practices maintain genetic diversity and limit inbreeding and relatedness after plants are brought into cultivation. We examine this question using Attalea crassispatha, a palm species with fewer than 100 palms surviving worldwide, and only 25 remaining in their native habitat. We sampled all accessible palms of this species (both in situ and ex situ) to (1) investigate how well garden collections capture in situ genetic diversity, (2) evaluate how well genetic diversity is carried forward into subsequent generations ex situ, (3) determine the number of wild and founding individuals contributing to ex situ breeding efforts, and (4) identify optimal breeding pairs that would maximize diversity and limit inbreeding. We found higher genetic diversity in situ and that current propagation practices lead to self-fertilization in the ex situ population and therefore fail to adequately steward genetic diversity in the conservation collection. Using relatedness analyses, we identified optimal breeding pairs in collections at different locations, highlighting the need for coordinated breeding efforts to maximize diversity ex situ. We also identified putative A. crassispatha that are genetically unrelated to the rest of the study cohort and are likely mislabeled. This study highlights the utility of genetic monitoring and the importance of careful coordination and record keeping within and among collections to ensure genetic diversity is maintained for future conservation efforts.